2016
DOI: 10.1016/j.jcol.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Association of sociodemographic and clinical factors with spirituality and hope for cure of ostomized people

Abstract: Objective To evaluate the sociodemographic and clinical factors related to patients with intestinal stoma and correlate them to the health locus of control, spirituality and hope for a cure. Method This study was conducted at the Polo of Ostomized Patients of the city of Pouso Alegre, Minas Gerais. Participants were 52 patients with intestinal stoma. The scale for Health Locus of Control, the Herth Hope Scale, and the Self-rating Scale for Spirituality were used for data collection. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
6
0
1
Order By: Relevance
“…Results showed that mean score on the Miller Hops Scale was significantly higher in male versus female patients. These results are similar to prior studies comparing outcomes of GCT using this instrument 11,57. Research suggests that males tend to resolve problems, adapt themselves to the new situation soon after going through the emotional phase 58…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Results showed that mean score on the Miller Hops Scale was significantly higher in male versus female patients. These results are similar to prior studies comparing outcomes of GCT using this instrument 11,57. Research suggests that males tend to resolve problems, adapt themselves to the new situation soon after going through the emotional phase 58…”
Section: Discussionsupporting
confidence: 87%
“…These results are similar to prior studies comparing outcomes of GCT using this instrument. 11,57 Research suggests that males tend to resolve problems, adapt themselves to the new situation soon after going through the emotional phase. 58 Our results showed that participants who had family caregivers gained a higher mean score on the Oxford Happiness Scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hope as a healing, dynamic and powerful healer, as one of the sources of coping, plays an important role in adapting to tensions and events (CARRETTA; RIDNER, 2014). Hope as a factor in the richness of life enables individuals to see themselves beyond the current state of view (MOREIRA et al, 2016).…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%
“…Como consequências podem surgir quadros de ansiedade e depres são que retardam ainda mais o processo de cicatrização da úlcera [9][10][11][12][13][14] .…”
unclassified